2022
DOI: 10.3390/ijerph191912967
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and Performance for Online Learning during COVID-19 Pandemic: A Meta-Analytic Evidence

Abstract: The COVID-19 pandemic prominently hit almost all the aspects of our life, especially in routine education. For public health security, online learning has to be enforced to replace classroom learning. Thus, it is a priority to clarify how these changes impacted students. We built a random-effect model of a meta-analysis to pool individual effect sizes for published articles concerning the attitudes and performance towards online learning. Databases included Google Scholar, PubMed and (Chinese) CNKI repository.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Their findings indicated that while online learning offers some benefits, this study mode is generally less effective when compared to face-to-face classroom learning. A similar conclusion was drawn by Liu et al (2022) through their meta-analytic assessment. Therefore, it becomes imperative to prioritise and rigorously evaluate the effectiveness of online learning methodologies.…”
Section: Online Learning Effectivenesssupporting
confidence: 78%
See 1 more Smart Citation
“…Their findings indicated that while online learning offers some benefits, this study mode is generally less effective when compared to face-to-face classroom learning. A similar conclusion was drawn by Liu et al (2022) through their meta-analytic assessment. Therefore, it becomes imperative to prioritise and rigorously evaluate the effectiveness of online learning methodologies.…”
Section: Online Learning Effectivenesssupporting
confidence: 78%
“…This, in turn, motivates their active participation and ultimately positively influences OLE and their perception of the benefits of online learning (Hongsuchon et al, 2022). Conversely, negative students' attitudes towards online learning are significantly related to poor online learning performance (Liu et al, 2022). High self-efficacy among postgraduate students encourages proactive OLB (Prior et al, 2016).…”
Section: Qae 322mentioning
confidence: 99%
“…In the winter of 2019, cases of the novel coronavirus were reported in Wuhan, Hubei Province, China [1]. At the beginning of the following year, the World Health Organization named the outbreak coronavirus disease (COVID-19) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The education sector represents a particularly high-risk group of building users, due to large numbers of learners commonly spending extended periods of time together in open lecture rooms. An example of how this risk has been addressed in the education sector can be seen in China, where many universities moved to online and hybrid teaching during the pandemic period [5,6]. However, complete separation of learners from a collective learning space is not always possible or practicable, so measures to improve the hygiene Environments 2023, 10, 182 2 of 14 of learning spaces have also needed to be introduced.…”
Section: Introductionmentioning
confidence: 99%